2002
DOI: 10.5713/ajas.2002.416
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Karanjin Using High Performance Liquid Chromatography in Raw and Detoxified Karanj (Pongamia glabra vent) Seed Cake

Abstract: Various products of karanj (Pongamia glabra) are utilized for industrial, health and animal agriculture applications in the Indian subcontinent. Despite a rich source of protein (CP, 28-34%), karanj cake was found to be slightly bitter in taste and toxic owing to the presence of flavonoid (Karanjin), restricting its safe inclusion in the livestock diets. Feeding trials with raw cake revealed its poor palatability and adverse performance among different categories of livestock including poultry. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Various methods, namely refluxing with 2% HCl (Mandal, 1985), solvent extraction, water leaching, autoclaving, acid and alkali treatment were adapted to detoxify karanja cake. Among all the methods, solvent extraction was found to remove karanjin efficiently (Prabhu et al, 2002) and is being widely used as a method to detoxify karanja cake. The information on the effect of feeding detoxified karanja cake (dKC) on testicular function were not reported in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods, namely refluxing with 2% HCl (Mandal, 1985), solvent extraction, water leaching, autoclaving, acid and alkali treatment were adapted to detoxify karanja cake. Among all the methods, solvent extraction was found to remove karanjin efficiently (Prabhu et al, 2002) and is being widely used as a method to detoxify karanja cake. The information on the effect of feeding detoxified karanja cake (dKC) on testicular function were not reported in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The seed kernel after extraction of oil is rich (around 30%) in crude protein (CP) and can be used in livestock and poultry feed as a protein source (Konwar et al, 1987;Vinay and Sindhu Kanya, 2008). However, raw expeller karanja cake is not commonly used as a feed for livestock because of the presence of toxic karanjin, pongamol and certain other polyphenolic compounds and poor palatability (Bringi and Mukerjee, 1987;Prabhu et al, 2002). These toxic factors can affect livestock performance and immune competence (Srivastava et al, 1990;Panda et al, 2004;Nagalakshmi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The karanjin concentration in the raw SKC has been reported to be within the range 0.10 and 1.32 g/kg (Prabhu et al., 2002; Panda et al., 2006). This disparity in karanjin content of raw cake may be because of residual karanjin left back in the cake by the extraction methods adopted.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports on quality control of karanjin from crude drugs of Karanj [Pongamia pinnata L. (Pierre)] (Ravikanth et al, 2009;Prabhu et al, 2002;Gore and Satyamoorthy, 2000) using TLC and HPLC methods. However pharmacokinetic study of JT using Karanjin as a marker has not been reported so far.…”
Section: Dermal Absorption Studiesmentioning
confidence: 99%